Papular Elastorrhexis: A Case Report of Rare Connective Tissue Naevus - Pudasaini, Prajwal; Pudasaini, Prashant; Bhatta, Rabi (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Papular Elastorrhexis (PE) is a connective tissue naevus that presents with non-follicular, yellow or white oval papules(1-5mm), mostly on the proximal extremities and the trunk. It is diagnosed with good clinical acumen and histologically with fragmented or decreased dermal elastic fibers. PE is difficult for clinicians to diagnose because of the rarity of the disease and non-specific presentation. Here we report a rare case of PE.